2017
DOI: 10.1038/ni.3686
|View full text |Cite|
|
Sign up to set email alerts
|

Human γδ T cells are quickly reconstituted after stem-cell transplantation and show adaptive clonal expansion in response to viral infection

Abstract: To investigate how the human γδ T cell pool is shaped during ontogeny and how it is regenerated after transplantation of hematopoietic stem cells (HSCs), we applied an RNA-based next-generation sequencing approach to monitor the dynamics of the repertoires of γδ T cell antigen receptors (TCRs) before and after transplantation in a prospective cohort study. We found that repertoires of rearranged genes encoding γδ TCRs (TRG and TRD) in the peripheral blood of healthy adults were stable over time. Although a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
320
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(365 citation statements)
references
References 52 publications
28
320
2
Order By: Relevance
“…Additionally, trans- rearrangements of shark IgM and IgW V segments to TCRδ diversity (D) and J segments from nearby immunoglobulin clusters are found in high levels 78 . These data suggest that a large proportion of γδ T cells act in an adaptive fashion, which has been borne out in several studies in mammals 92,93 . Future work should be done to analyse γδ T cell adaptive responses in ectotherms, which is just beginning to be accomplished 93 .…”
Section: Evolution Of Antigen Receptorssupporting
confidence: 66%
See 1 more Smart Citation
“…Additionally, trans- rearrangements of shark IgM and IgW V segments to TCRδ diversity (D) and J segments from nearby immunoglobulin clusters are found in high levels 78 . These data suggest that a large proportion of γδ T cells act in an adaptive fashion, which has been borne out in several studies in mammals 92,93 . Future work should be done to analyse γδ T cell adaptive responses in ectotherms, which is just beginning to be accomplished 93 .…”
Section: Evolution Of Antigen Receptorssupporting
confidence: 66%
“…These data suggest that a large proportion of γδ T cells act in an adaptive fashion, which has been borne out in several studies in mammals 92,93 . Future work should be done to analyse γδ T cell adaptive responses in ectotherms, which is just beginning to be accomplished 93 . This is especially of interest in cartilaginous fish, where the TCRγ V genes have been definitively shown to hypermutate, similar to what has been detected in immunoglobulin genes 78,94 .…”
Section: Evolution Of Antigen Receptorssupporting
confidence: 66%
“…In addition, adoptive transfer T cells from lymph nodes rescued the skin inflammation in IL-36R −/− mice. Our findings with γδ T cells might better translate to humans because circulating Vγ9/Vδ2 and Vδ1 + γδ T cell populations in human blood have been increasingly recognized to participate in the immune response to pathogens (Davey et al, 2017; Ravens et al, 2017). Finally, in response to a deeper subcutaneous S. aureus challenge in mice, adipocytes produced the antimicrobial peptide CRAMP to promote bacterial clearance, but a role for IL-36 or other IL-1 family members was not evaluated (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…After allo-HCT, CMV induced vδ1+ T cells are capable of recognizing both CMV-infected cells and primary leukemic blasts ● [8, 91]. Next generation sequencing of the γδTCRs revealed that CMV reactivation post allo-HCT induced a clonal proliferation of distinct γδT cell clones, suggesting a γδTCR-mediated response of γδT cells upon CMV infection ●● [92]. Longitudinal analysis of γδT cells in series of allo-HCT recipients demonstrated that γδT cell numbers are significantly higher in recipients with CMV viraemia as compared to recipients without CMV reactivation [9395, 91].…”
Section: 3 Potential Strategies To Simultaneously Enhance Nk and γδmentioning
confidence: 99%
“…A factor to consider is that the composition and function of the tumor-infiltrating lymphocyte repertoire is different as compared to that of circulating lymphocytes [109]. Recently developed high-resolution methods for cell analysis like Cytometry by time of Flight (CyTOF) ● [110], next-generation sequencing of γδ TCRs[92] as well as single-cell RNA-seq [109] have all contributed to new insights in complex (innate) immunological networks.…”
Section: 4 Concluding Remarksmentioning
confidence: 99%